Pengaruh Kepercayaan Diri terhadap Keterampilan Menyimak dan Berbicara Murid dalam Pembelajaran Bahasa Indonesia - Devi Irma Purwati (Dar El-Falah, 2026)
This study aims to analyze the effect of self-confidence on the listening and speaking skills of students in Indonesian language learning in Grade V at MIN 2 Mojokerto. The quantitative-associative research involved a population of 165 students, with a sample of 83 respondents using proportional random sampling. Data were collected using questionnaires, documentation, and observation. Hypothesis testing was conducted using simple linear regression analysis. The results of the study indicate that: 1) There is an effect of self-confidence on the listening skills of students in Indonesian language learning in Grade V at MIN 2 Mojokerto, as the t-count value ˃ t-table (8.094 > 1.990) and F-count = 65.507 with a p-value of 0.000, which is smaller than α = 0.05 (0.000 ˂ 0.05). The coefficient of determination (R Square) is 0.447. The obtained linear regression equation is Ŷ = 6.929 + 0.868X. 2) There is an effect of self-confidence on the speaking skills of students in Indonesian language learning in Grade V at MIN 2 Mojokerto, because the calculated t-value ˃ t-table (7.161 ˃ 1.990) and the calculated F-value = 51.284 with a p-value of 0.000, which is smaller than α = 0.05 (0.000 ˂ 0.05). With a coefficient of determination (R Square) of 0.388. The obtained linear regression equation is Ŷ = 16.763 + 0.694X.